Augmented Reality-assisted Problem Based Learning E-Module to improve Problem-Solving Skills - Zurienia Mimi Bibiyana; Fatchur Rohman; Mimien Henie Irawati Al-Muhdhar (Jurnal Pendidikan Sains, 2021)
Abstract: Problem-solving skills in the field of Biology have an important role in representing problems, finding relationships, making predictions, and verifying or checking solutions. This study aims to implement an augmented reality-assisted problem-based learning e-module on bioindicator materials to improve problem-solving skills. The research method used is a pre-experimental one-group pretest-posttest design involving 29 biology students at the State University of Malang for the 2020/2021 academic year. Paired T-Test results show that the e-module has a significant effect on improving students' problem-solving skills.Abstrak: Keterampilan pemecahan masalah pada bidang Biologi memiliki peran penting dalam merepresentasikan masalah, mencari hubungan, membuat prediksi, dan memverifikasi atau memeriksa solusi. Penelitian ini bertujuan untuk mengetahui efektifitas e-module pembelajaran berbasis masalah berbantuan augmented reality melalui implementasi dalam pembelajaran untuk meningkatkan keterampilan pemecahan masalah. Metode penelitian yang digunakan adalah pre-experimental one-group pretest-posttest design dengan melibatkan 29 mahasiswa biologi Universitas Negeri Malang tahun ajaran 2020/2021. Hasil uji T berpasangan menunjukkan implementasi e-module berpengaruh secara signifikan untuk meningkatkan keterampilan pemecahan masalah mahasiswa.